2023
DOI: 10.3389/fmicb.2023.1304621
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic and postbiotic analytical methods: a perspective of available enumeration techniques

Marie-Eve Boyte,
Andrzej Benkowski,
Marco Pane
et al.

Abstract: Probiotics are the largest non-herbal/traditional dietary supplements category worldwide. To be effective, a probiotic strain must be delivered viable at an adequate dose proven to deliver a health benefit. The objective of this article is to provide an overview of the various technologies available for probiotic enumeration, including a general description of each technology, their advantages and limitations, and their potential for the future of the probiotics industry. The current “gold standard” for analyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 127 publications
(202 reference statements)
0
0
0
Order By: Relevance
“…For these reasons, plate count is nowadays considered more of an estimate than an actual quantification of viable cells ( Davey, 2011 ; Boyte et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For these reasons, plate count is nowadays considered more of an estimate than an actual quantification of viable cells ( Davey, 2011 ; Boyte et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…An alternative method of great interest in the field of probiotics is flow cytometry ( Adan et al, 2017 ; Pane et al, 2018 ; Sielatycka et al, 2021 ; Boyte et al, 2023 ; Pereira et al, 2023 ; Tracey et al, 2023 ) due to its rapid and automatic results. Staining the cells with fluorescent dyes prior to measurement can provide valuable information.…”
Section: Introductionmentioning
confidence: 99%
“…Because the probiotic products that were used in the stability monitoring experiment were multi-strain products, it was not possible to compare the viable counts to plate counts. Nonetheless, plate count and viability PCR measure viability differently where plate count methods rely on cultivability while viability PCR relies on membrane integrity as a measure of viability (Boyte et al, 2023). Previous studies have reported discrepancies in viable counts determined using culturedependent versus culture-independent methods, especially following storage (Fiore et al, 2020;Wendel, 2022;Shehata et al, 2023).…”
Section: Frontiers In Microbiologymentioning
confidence: 99%
“…PCR based methods are widely used for probiotic identification including species-specific and strain-specific methods (Morovic et al, 2016;Kim et al, 2020;Shehata et al, 2021a,b;Kim et al, 2022). For probiotic enumeration, plate count methods are currently the most commonly used methods for probiotic quantification (Davis, 2014;Weitzel et al, 2021;Boyte et al, 2023), however, other cultureindependent methods such as flow cytometry and PCR based methods are also emerging for probiotic enumeration (Boyte et al, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…The conventional plate count method may not effectively capture the entire spectrum of microbial activity, particularly for those cells termed “viable but non-culturable” (VBNC). This has driven the exploration of alternative methods that can provide a more comprehensive and nuanced picture of the microbial viability ( Boyte et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%